(untitled) (Research, Society and Development, 2022)
This paper seeks to contribute to the discussions concerning the study area of colors. Bearing in mind that the psychological effects of colors on individuals’ cognition are gaining more and more space, whether in psychology itself or the areas of marketing and product development. Therefore, we sought to identify how color psychology has been debated in the scientific community. In this way, the present article aims to understand how studies on the psychological dimension of colors in scientific works have gone from their first publication to the present, more specific 2020. A systematic bibliographic review was carried out that mapped scientific papers, dissertations, and theses, resulting in 116 texts. The methodology used is descriptive, quantitative, and qualitative in its approach. As a result, the research determined 2006 as a marker for developing and disseminating publications in scientific paper format in the area. Also, we found a predominance of experimental theory research, with primarily qualitative approaches and exploratory objectives. We found that the focus of the authors is to research universities. We found the leading countries with research in color psychology, such as the United States and Brazil.